The Black Witch - Book 1 - Forest, Laurie (Don Mills, Ontario, Canada Harlequin Teen, 2018)
Elloren Gardner is the granddaughter of the last prophesied Black Witch, Carnissa Gardner, who drove back the enemy forces and saved the Gardnerian people during the Realm War. But while she is the absolute spitting image of her famous grandmother, Elloren is utterly devoid of power in a society that prizes magical ability above all else. When she is granted the opportunity to pursue her lifelong dream of becoming an apothecary, Elloren joins her brothers at the prestigious Verpax University to embrace a destiny of her own, free from the shadow of her grandmother's legacy.
Keywords: Witches -- Juvenile fiction; Witches -- Fiction; Fantasy